The qussas of early Islam - Armstrong, Lyall R. (Islamic History and Civilization, 2017)
The Islamic qāṣṣ (preacher/storyteller) has been viewed most commonly as a teller of stories, primarily religious in nature and often unreliable. Building on material of over a hundred quṣṣāṣ from the rise of Islam through the end of the Umayyad period, this book offers the most comprehensive study of the early Islamic qāṣṣ to-date. By constructing profiles of these preachers/ storytellers and examining statements attributed to them, it argues that they were not merely storytellers but were in fact a complex group with diverse religious interests. The book demonstrates how the style and conduct of their teaching sessions distinguished them from other teachers and preachers and also explores their relationship with early religio-political movements, as well as with the Umayyad administration.